Separability of the third-order differential operator given on the whole plane - Suleimbekova, A.O. (Bulletin of the Karaganda University. Mathematics Series, 2022)
In this paper, in the space L2(R2), we study a third-order differential operator with continuous coefficients in R (-∞ , +∞). Here, these coefficients can be unlimited functions at infinity. In addition under some restrictions on the coefficients, the bounded invertibility of the given operator is proved and a coercive estimate is obtained, i.e. separability is proved.